Evolution Characteristics of Sand-Dust Weather Processes in China During 1961–2020 - Duan, Haixia; Hou, Wei; Wu, Hao; Feng, Taichen; Yan, Pengcheng (Frontiers in Environmental Science, 2022)
The sand-dust weather is a disastrous weather in spring in China, which seriously endangers agricultural production, transportation, air quality, and even people's lives and property, thus receiving sustained and extensive concern. Currently, few studies have been conducted to analyze sand-dust events in North China from the perspective of sand-dust processes. Although there are a few studies on the spatio-temporal variation characteristics of sand-dust processes, they are mainly based on outdated data or case studies of major sand-dust events. In this study, the evolution characteristics of sand-dust processes in China in recent 60 years are studied based on the identification method and several characteristic quantities (including duration and impact range) of sand-dust weather processes defined in the Operational Regulations of Monitoring and Evaluation for Regionally Weather and Climate Processes newly issued by the China Meteorological Administration in 2019. Firstly, through statistics, we obtain the annual occurrence frequency, annual days and the annual number of affected stations of sand-dust processes (including sand-dust storm, blowing sand and suspended dust) from January 1961 to May 2021. Based on the moving t-test technique and the ensemble empirical mode decomposition, we analyze evolution trends and probability distribution characteristics of annual occurrence frequency, annual days and annual number of affected stations of sand-dust processes. In addition, we investigate the start time of the first and the last dust processes in each of the past 60 years, as well as the seasonal distribution characteristics of sand-dust processes. The results show that under the background of global warming, the sand-dust weather in China tends to decrease significantly. Specifically, the annual occurrence frequency and annual days show a trend of increasing first and decreasing later, and the significant turnarounds of annual number of dust processes occurred in the 1980s and around 2010. Moreover, the sand-dust processes tend to start later and end earlier. The sand-dust processes mainly concentrate in March–May, with the highest occurrence probability in April.